Some Generalizations of Mirzakhani's Recursion and Masur-Veech Volumes via Topological Recursions - Fuji, Hiroyuki; Manabe, Masahide (Symmetry, Integrability and Geometry: Methods and Applications, 2024)
Via Andersen-Borot-Orantin's geometric recursion, a twist of the topological recursion was proposed, and a recursion for the Masur-Veech polynomials was uncovered. The purpose of this article is to explore generalizations of Mirzakhani's recursion based on physical two-dimensional gravity models related to the Jackiw-Teitelboim gravity and to provide an introduction to various realizations of topological recursion. For generalized Mirzakhani's recursions involving a Masur-Veech type twist, we derive Virasoro constraints and cut-and-join equations, and also show some computations of generalized volumes for the physical two-dimensional gravity models.